Empathetic factors and influences on physical performance: a topical review - Behm, D. G.; Carter, T. B. (Frontiers in Psychology, 2021)
Performance is dependent upon both physical and psychological factors. As a social animal, human behaviors are influenced by interactions with others. Empathy is based on social interactions and is defined as the understanding, awareness of, sensitivity to, and ability to vicariously experience the feelings, thoughts, and experience of another. There are few investigations on the influence of empathy in relation to individual and team performance and activity. There is some initial research suggesting that observing sad photos or videos or fatiguing exercise can adversely affect subsequent performance. Possible mechanisms may be attributed to mirror neurons or the affordance competition hypothesis. The relative degree of empathetic influences can be modulated by sex, age, personal familiarity, cultures and other factors. With the limited research in sport and exercise science, there is a need for more research to investigate the role of empathy on individual and team performances. The objective of this topical review was to examine the possible effects of empathy on physical performance, the potential underlying mechanisms and influencing variables moderating the association between empathy and performance?